Digital Interventions to Save Lives From the Opioid Crisis Prior and During the SARS COVID-19 Pandemic: A Scoping Review of Australian and Canadian Experiences - Donnell, Andrea; Unnithan, Chandana; Tyndall, Jessica; Hanna, Fahad (Frontiers in Public Health, 2022)
Background. The potential for digital initiatives for opioid harm reduction is boundless. However, synthesised evidence on current interventions and their efficacy are emerging. This scoping review is an effort to aggregate Canadian and Australian digital health initiatives used to prevent opioid-related deaths and minimise harm, prior and particularly during the pandemic of SaRs-Covid-19, when the crisis escalated. Methods. The Joanna Briggs Institute’s methodological framework for conducting scoping reviews was used. Peer reviewed and grey literature published between January 2016 to October 2021 were included. Search translation was performed across CINAHL, Cochrane, SCOPUS, MEDLINE Complete and ProQuest Public Health with consistent use of key search terms. Citation checks were also conducted. Studies included were written in English and reported on digital technologies to prevent opioid-related harm and/or mortality in participants aged 18years or older in Australia and Canada. Results. A total of 16 publications were included in the final analysis (Australia = 5; Canada =11). The most frequently reported digital technologies were telehealth to support access to treatment (n=3) and mobile applications for overdose monitoring and prevention (n=3). Telehealth delivered opioid replacement therapy demonstrated equal outcomes and treatment retention rates compared to in person and mobile applications for overdose monitoring demonstrated life saving capability through direct linkages with emergency response services. Conclusions. Digital interventions to minimise opioid crisis related harm and overdose prevention are fast emerging in Australia and Canada. During the pandemic, the crisis has escalated in both countries as a public health emergency, and different initiatives were trialled. Digital harm reduction solutions via mobile apps (or SaaS solutions) were found to have the potential to prevent accidental overdose deaths and save lives, if rendered through privacy preserved, secure and trust enabled methods that empower users. Knowledge sharing amongst the 2 countries, relating to suitable interventions, may add significant value in combatting the escalating opioid crisis in the post pandemic era.